2010
DOI: 10.5202/rei.v2i1.27
|View full text |Cite
|
Sign up to set email alerts
|

The impact of international trade flows on economic growth in Brazilian states

Abstract: This paper explores the impact of trade openness on the economic growth of Brazilian states according to their initial income level. This empiri- cal study covers 26 Brazilian states over the period 1989-2002. Growth rates of Brazilian states are modeled as dependent on international trade flows and a set of control variables such as initial income level, human capital, private and public physical capital, growth rate of labor force and a number of inter- action terms with trade openness. This empirical analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Most of the studies try to assess whether the growth effects of trade with developed and with developing countries (LA region included) are different from one another. Daumal and Ozyurt () explore the impact of trade openness, as trade ratios, on the economic growth, as per capita GDP , of Brazilian states according to their initial income level. The empirical study was carried out over the period 1989–2002, and their results suggested that openness was more beneficial to states with a high level of initial per capita income and therefore contributes to increased regional disparities in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies try to assess whether the growth effects of trade with developed and with developing countries (LA region included) are different from one another. Daumal and Ozyurt () explore the impact of trade openness, as trade ratios, on the economic growth, as per capita GDP , of Brazilian states according to their initial income level. The empirical study was carried out over the period 1989–2002, and their results suggested that openness was more beneficial to states with a high level of initial per capita income and therefore contributes to increased regional disparities in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…First, validity of lagged values instrumenting for the differenced variable depends crucially on their being uncorrelated with differenced error term (εit−εit−1) which can be tested using Sargan test of overidentifying restrictions (Sargan, 1958;Santos, 2015). Second, instrument validity depends upon the assumption of error term being serially uncorrelated (Daumal and Ozyurt, 2010;Sharma, 2018). In order to test for serial correlation, the Arellano and Bond (XXXX) test was used.…”
Section: Methodsmentioning
confidence: 99%
“…The increase in competition has been a driver for firms to be innovative. The innovative changes especially in technologies, have led to the growth of international trade (Daumal, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%